Lessons learned: engaging older adults in generative design sessions for a digital messaging system - Edugyan, Abena; Papallas, Andreas; Zaphiris, Panayiotis (My University, 2018)
The global population continues to age within an increasingly digitally connected society. Because of the ubiquity of technology, the needs, experiences and values of older adults should be considered to ensure they are not excluded from any advantages the digital society may provide. Engaging in generative design research allows users to collaborate with designers to uncover those needs as well as discover creative solutions to design problems. This paper explores the results of three generative design sessions conducted with older adults to gain insight into the feasibility of a digital messaging system designed to foster their inclusion in the digital society. Immersion and card sort sessions revealed the value placed in face-to-face communication with peers, while the card sort and brainstorm sessions highlighted health as a possible theme to be further explored. Additionally, the brainstorm session concluded with the creation of a rudimentary prototype, reinforcing the creativity older adults can bring to the design process. While the feedback generated from the sessions may not have supported the initial idea, they showed that the contribution of older adults in the design research process should not be understated.
Keywords: Generative design; Older adults; Digital society